Leaf microbiome assembly is linked to plant phylogeny - Pankaj K. Singh; Catarina S. C. Martins; Ramesha H. Jayaramaiah; Eleonora Egidi; Catriona Macdonald; Juntao Wang; Chao Xiong; Bruna Batista; Galaxy Qui; Peter B. Reich; Manuel Delgado-Baquerizo; Brajesh K. Singh (Plant and Soil, 2026)
Background and aims The plant microbiome is considered as an extended part of the plant genome, and it provides key functions in regulating plant fitness, and stress tolerance. Plants and associated microbiomes have co-evolved over millennia, yet evidence for a strong influence of plant phylogeny on their microbiomes is largely lacking. Our aim was to assess relative contributions of soil microbial diversity, host phylogenetic relatedness, host niches and environmental disturbance on plant microbiome assembly. Methods We conducted a full factorial experiment that included three levels of soil microbial diversity, five plant species from three functional groups (C3, C4, and C3 nitrogen-fixing), and two moisture availability levels. Results Our results showed that host identity and plant functional group exerted the strongest effect on leaf microbial assembly, while root and soil microbiomes showed less sensitivity to host selection. The initial soil microbial diversity and composition significantly impacted soil and root microbial composition, but not leaf microbiomes. Importantly, we observed significant positive linkage between host phylogeny distance and Bray–Curtis dissimilarity index in leaf microbiomes. This finding was further validated through analysis of microbiome data from seven plant species grown across different field and environmental conditions. There was no significant impact of short-term water stress on plant microbial communities. Conclusions By providing empirical evidence for important role of host selection in shaping plant microbiomes, this study advances our fundamental knowledge of plant–microbe interactions and their co-evolutionary relationships and enhances our ability to develop future tools harnessing plant microbiome to improve plant health and productivity.